The variability of sagittal spino-pelvic mobility in Indian population - N., Sukesh A.; Varughese, Jacob; Thomas, Appu B.; Theruvil, Bipin (International Journal of Research in Orthopaedics, 2020)
Background: Abnormal spino-pelvic mobility is increasingly recognized as a leading cause for hip instability following arthroplasty. Methods: We studied the lateral spino-pelvic radiographs of 90 patients, with no spine/hip pathology in standing and sitting positions. We measured the change in sacral slope and grouped them into three spino-pelvic patterns. Results: We found that 50% of study subjects had normal spino-pelvic mobility. The remaining 50% were either hypermobile (24%) or stiff (26%). The stiff spines were either fixed (11%) or hypomobile (15%). Conclusions: Our study shows that in a normal population without any prior hip/spine pathology a significant percentage (50%) have abnormal spino-pelvic mobility. The significance of spinal stiffness in younger age group need to be looked further to make any changes in acetabular cup placement during hip replacement.